2013
DOI: 10.7567/jjap.52.11nb09
|View full text |Cite
|
Sign up to set email alerts
|

Properties of WO3-x Electrochromic Thin Film Prepared by Reactive Sputtering with Various Post Annealing Temperatures

Abstract: The WO3-x thin films were prepared on indium tin oxide (ITO) coated glass at 0.7 oxygen flow ratio [O2/(Ar+O2)] using the facing targets sputtering (FTS) system at room temperature. In order to obtain the annealing effect, as-deposited thin films were annealed at temperatures of 100, 200, 300, 400, and 500 °C for 1 h in open air. The structural properties of the WO3-x thin film were measured using an X-ray diffractometer. The WO3-x thin films annealed at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…XRD demonstrates that the WO 3 /IAI is similar to those deposited on single ITO substrate (only the characteristic peaks of the ITO and the contribution of the glass substrate are detectable). This is consistent with the literature re sults whereas minimal temperature of 300 C is required for the preparation of crystalline WO 3 by magnetron sputtering [35,36]. For the NiO x /IAI films, only the (111) Bragg's peak of the NiO halite structure is visible at around 2q 37 in addition to the ITO and glass contribution.…”
Section: Characterization Of the Nio X And Wo 3 Films As The Iai Filmsupporting
confidence: 91%
“…XRD demonstrates that the WO 3 /IAI is similar to those deposited on single ITO substrate (only the characteristic peaks of the ITO and the contribution of the glass substrate are detectable). This is consistent with the literature re sults whereas minimal temperature of 300 C is required for the preparation of crystalline WO 3 by magnetron sputtering [35,36]. For the NiO x /IAI films, only the (111) Bragg's peak of the NiO halite structure is visible at around 2q 37 in addition to the ITO and glass contribution.…”
Section: Characterization Of the Nio X And Wo 3 Films As The Iai Filmsupporting
confidence: 91%
“…Results demonstrated that the swelling equilibrium appeared to have no significant variation after 3 cycles, indicating the repeatability of the thermo-stimulated autoshrinkage of PNI-HA. [27] The tissue adhesion of PNI-HA was quantificationally measured using the modified tensile testing method (Figure 3D). All hydrogels were observed to exhibit temperature-regulated adhesive strength.…”
Section: Pni-ha Has Thermo-stimulated Auto-shrinkage and Tissue Adhesionmentioning
confidence: 99%
“…The spirit of the research was to manufacture the WO 3 film that combines the positive features of the crystalline and amorphous films, providing gradual changes in the film crystalline structure along the film thickness. In addition, according to the previous reports, 400 °C is in favor of WO 3 to obtain a crystalline structure. , Thus, this temperature is chosen to prepare the WO 3 film with a crystalline structure in this work.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…In addition, according to the previous reports, 400 °C is in favor of WO 3 to obtain a crystalline structure. 21,22 Thus, this temperature is chosen to prepare the WO 3 film with a crystalline structure in this work.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%